The WNT target SP5 negatively regulates WNT transcriptional programs in human pluripotent stem cells. Issue 1 (December 2017) - Huggins, Ian; Bos, Tomas; Gaylord, Olivia; Jessen, Christina; Lonquich, Brianna; Puranen, Angeline; Richter, Jenna; Rossdam, Charlotte; Brafman, David; Gaasterland, Terry; Willert, Karl
Abstract The WNT/β-catenin signaling pathway is a prominent player in many developmental processes, including gastrulation, anterior–posterior axis specification, organ and tissue development, and homeostasis. Here, we use human pluripotent stem cells (hPSCs) to study the dynamics of the transcriptional response to exogenous activation of the WNT pathway. We describe a mechanism involving the WNT target geneSP5 that leads to termination of the transcriptional program initiated by WNT signaling. Integration of gene expression profiles of wild-type andSP5 mutant cells with genome-wide SP5 binding events reveals that SP5 acts to diminish expression of genes previously activated by the WNT pathway. Furthermore, we show that activation of SP5 by WNT signaling is most robust in cells with developmental potential, such as stem cells. These findings indicate a mechanism by which the developmental WNT signaling pathway reins in expression of transcriptional programs. WNT/β-catenin signaling is an essential regulator of many developmental processes. Here, the authors provide evidence that activation of the WNT in human pluripotent stem cells leads to expression WNT target geneSP5, which then acts to diminish expression of active WNT target genes.